2018
DOI: 10.3350/cmh.2017.0077
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of psoas muscle thickness for the diagnosis of sarcopenia in patients with liver cirrhosis

Abstract: Background/AimsThe most widely used method for diagnosing sarcopenia is the skeletal muscle index (SMI). Several studies have suggested that psoas muscle thickness per height (PMTH) is also effective for detecting sarcopenia and predicting prognosis in patients with cirrhosis. The aim of this study was to evaluate the optimal cutoff values of PMTH for detecting sarcopenia in cirrhotic patients.MethodsAll cirrhotic patients who underwent abdominal computed tomography (CT) scan including L3 and umbilical levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 45 publications
(40 reference statements)
3
97
1
1
Order By: Relevance
“…The prognostic value of TPMT was already shown in patients with ascites and TPMT was also associated with mortality in patients on the liver transplant waiting list. Gu et al compared SMI and TPMT measurements and found good correlation between the two variables and described similar rates for sarcopenia when using SMI (37%) and TPMT (between 35% and 44%) when using gender‐specific cut‐offs for men (17.3 mm/m) and for women (10.4 mm/m) …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The prognostic value of TPMT was already shown in patients with ascites and TPMT was also associated with mortality in patients on the liver transplant waiting list. Gu et al compared SMI and TPMT measurements and found good correlation between the two variables and described similar rates for sarcopenia when using SMI (37%) and TPMT (between 35% and 44%) when using gender‐specific cut‐offs for men (17.3 mm/m) and for women (10.4 mm/m) …”
Section: Discussionmentioning
confidence: 95%
“…Importantly, the TPMT was an independent risk factor for mortality on top of MELD or MELD‐Na . The detrimental impact of sarcopenia on survival has subsequently been confirmed by several studies . Thus, strategies to improve muscle wasting are now widely accepted as important treatment goals in ACLD patients, however standardized and clinically feasible assessment of muscle mass is still lacking and randomized controlled trials on specific interventions are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity and specificity of MAC were similar to values obtained using more expensive predictors. A recent study evaluating the role of psoas muscle thickness as a function of height as a sarcopenia predictor in liver cirrhosis found sensitivity and specificity of 65.3% and 76.3% for men and 31.2% and 90.6% for women, respectively . It should be emphasised that the measure proposed was obtained through ionising radiation examinations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluating the role of psoas muscle thickness as a function of height as a sarcopenia predictor in liver cirrhosis found sensitivity and specificity of 65.3% and 76.3% for men and 31.2% and 90.6% for women, respectively. 39 It should be emphasised that the measure proposed was obtained through ionising radiation examinations. In another study aiming to identify sarcopenia predictors by applying ultrasound-based measurements of peripheral muscle mass combined with BMI, the model had sensitivity and specificity of 72% and 78% for men and 94% and 76% for women, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Schweitzer et al revealed that areas at the mid-thigh provided better evidence than lumbar muscle areas for assessments of total skeletal muscle volume [81]. In addition, studies have supported the fact that a reduction in the mid-thigh muscle CSA obtained using a CT scan is better than a low BMI for predicting mortality in pati Furthermore, CT measurements of psoas muscle thickness have been used to assess sarcopenia and predict morbidities in certain patients with conditions (e.g., colorectal cancer, ovarian cancer) and those undergoing certain treatments (e.g., colorectal surgery, lung transplantation) [85][86][87]. This measurement is sometimes obtained at the L3 level on the first image in the craniocaudal direction, wherein the two transverse processes are visible [88,89].…”
Section: Image Detection Methodsologies For Spinal Sarcopeniamentioning
confidence: 99%